Smart city e capitalismo de vigilância : desdobramentos do controle social a partir do extrativismo de dados - Santos, Priscilla Macêdo (2022)
The present work was prepared from the observation of the growing and lucrative phenomenon of smart cities across the globe to the detriment of the “obsolete” traditional city model, as a symptom of the technopolitical advance for the management of cities. In this analysis, we chose to follow the path of power relations established in this scenario, based on the recognition of new forces acting on urban public administration, according to the establishment of technocratic governments driven by the multibillion-dollar sector of big techs. It was noted, therefore, that the exercise of power occurs, in this context, through the control and surveillance of events, objects and people through the extraction of a large volume of data explored daily, forming the big data. Through the recognition of these factors, the approach taken started from the unders-tanding of this phenomenon as a political agenda guided by neoliberalism, acting by the logic of surveillance capitalism that explores the human experience in smart cities to exercise modu-lation of behaviors and modification of subjectivities. Thus, the imposition of perspectives from the global North was verified with the imposition of ways of life and epistemologies from the use of technological devices exported to the global South, working, at the end of this work, on the need to foster perspectives of the margin, who think of alternatives and democratic uses of technology in order to redistribute power to the hands of those who provide the raw material of data with their own experience. Therefore, the developed research is entirely aligned with the need for academic studies regarding the practices of social control investigated by the criminal sciences, mainly in the context of violence generated by the exercise of power. Therefore, the bibliographic technique was used for this purpose through the hypothetical-deductive method in order to verify the projected hypothesis